(Re)locating New Zealand School Principals as Leaders in School Networks: Leadership in Communities of Learning - Dibben, Michelle (Auckland University of Technology, 2019)
Since 2014, Ministry of Education (MoE) policy in New Zealand has encouraged schools to work collaboratively together in formalised networks known as Communities of Learning (CoLs). The Investing in Educational Success (IES) initiative signals a new direction for New Zealand schools, placing school principals as leaders across a network, with the key aim of lifting student achievement through improved teacher effectiveness. Network leadership is relatively new to educational discourse and requires understanding of the complexities involved in leading across multiple sites. This study explores the experiences of three CoL leaders as they navigate the space between policy expectations and the reality of network practice. The research methodology focused on a collective case study design so that similarities and differences could be extrapolated from cross-case analysis to explore the lived experiences of CoL leaders in their network contexts. Following semi-structured interviews with each CoL leader, the principal members of each CoL were invited to complete a questionnaire to gain their perceptions of the role of CoL leader. Throughout the research process, document review and analysis supported and complemented exploration of the key themes arising from literature review and case study findings, and highlighted the challenges encountered through network activity. The findings of this study identified the leadership approaches, and network practices, necessary for effective CoL partnerships. The leadership approaches included: system leadership, relational leadership, and collaborative leadership. Consideration of the following constituted the network practices relevant to engaging and sustaining collective enterprise: establishing collaborative cultures, fostering the development of social capital, and facilitating opportunities for the emergence of hybrid configurations of leadership. Aligning policy with practice provided the greatest challenge, particularly in respect of operating within two systems – self-managing schools (a product of Tomorrow’s Schools reforms) and networked structures (a result of the IES initiative). Despite recent MoE policy decisions preventing the formation of new CoLs, this study still has implications for school leaders as they work in partnerships with others beyond their own school site.
Keywords: Communities of learning; Networks; Collaboration; System leadership